Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Motivasi Belajar Fisika Siswa SMA Negeri 17 Gowa - Hasrah, Hasrah; Hasyim, Mutahharah; Rapiuddin, Rapiuddin (Universitas Negeri Makassar, 2025)
Abstract. This research is action research carried out in two cycles which aims to determine the increase in student learning motivation. The subjects in this research were all students of class X Science 3 SMA Negeri 17 Gowa, totaling 25 students. This research was conducted in 2 cycles. Data collection was carried out by making observations. The research results showed that students' learning motivation in cycle I obtained an average score of 71.70 which was in the high category. Meanwhile, motivation in cycle II average score was 77.33 which was in the high category. In cycle I, there were 5 students' learning motivation in the very high category and 20 students in the high category, while in cycle II, 14 students' learning motivation was in the very high category and 11 students were in the high category. It can be concluded that the application of the problem-based learning model (Problem Based Learning) can increase student learning motivation. Keywords: Motivation, Physics, Problem Based Learning